2019
DOI: 10.1159/000499574
|View full text |Cite
|
Sign up to set email alerts
|

Association of Acute Kidney Injury with Cardiovascular Events and Death in Systolic Blood Pressure Intervention Trial

Abstract: Rationale and Objective: In the Systolic Blood Pressure Intervention Trial, the possible relationships between acute kidney injury (AKI) and risk of major cardiovascular events and death are not known. Study Design: Post hoc analysis of a multicenter, randomized, controlled, open-label clinical trial. Setting and Participants: Hypertensive adults without diabetes who were ≥50 years of age with prior cardiovascular disease, chronic kidney disease (CKD), 10-year Framingham risk score > 15%, or age > 75 years wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…AKI itself is a known predictor of death and CVD events, and our data demonstrate an additive risk of sepsis and AKI for postdischarge events. 14 , 15 , 16 The consistent association between sepsis and adverse outcomes across subgroups with and without various manifestations of critical illness helps to demonstrate the potential hazard from sepsis beyond the known harmful effects of its downstream complications and argues against the presence of critical illness itself as the sole mediator of this association.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AKI itself is a known predictor of death and CVD events, and our data demonstrate an additive risk of sepsis and AKI for postdischarge events. 14 , 15 , 16 The consistent association between sepsis and adverse outcomes across subgroups with and without various manifestations of critical illness helps to demonstrate the potential hazard from sepsis beyond the known harmful effects of its downstream complications and argues against the presence of critical illness itself as the sole mediator of this association.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 12 , 13 Complications of sepsis such as AKI have likewise been associated with a higher risk of subsequent CVD events. 14 , 15 , 16 If the elevated risk of CVD events after recovery from sepsis was amenable to preventative therapy, then cardiovascular prevention strategies might be an important component of the care of survivors of sepsis.…”
mentioning
confidence: 99%
“…Similar findings were demonstrated by Pablo et al, who examined > 19,000 patients and showed that MACE in the follow-up was linked with dyslipidemia and lower LVEF [ 24 ]. Also, in another study evaluating the impact of impaired renal function on cardiovascular outcomes, the investigators have shown that impaired renal functions were associated with higher rates of acute coronary syndrome, myocardial infarction, decompensated heart failure, stroke and death [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A similar observation has also been reported in a study by Tonelli et al [11] which revealed that elderly male patients were more susceptible to AKI than other groups investigated. Studies have also shown that the incidence of AKI is rising among the elderly patients due to combinations of multiple diseases which include diabetes, vascular diseases and chronic kidney diseases [12,13]. These patients also have a higher degree of exposure to several nephrotoxic agents during the diagnostic procedures and drug administration [14].…”
Section: Discussionmentioning
confidence: 99%